Determinant Factors of Contact Dermatitis on Tofu Factory Workers in Kupang City - Tanesab, Delto Loisandro; Syamruth, Yendris K.; Riwu, Yuliana Radja (Lontar : Journal of Community Health, 2023)
Contact dermatitis is a skin inflammation due to exposure to certain substances which can cause irritation or allergic reactions. An initial survey of several tofu factories in Kupang City found that workers with dermatitis contact symptoms such as peeling skin, itching, and dry and scaly skin. The prevalence of allergic skin diseases such as contact dermatitis in Kupang City in 2018 was (5,5%). This study aims to determine the associated factor with the incidence of contact dermatitis in tofu factory workers. The research used a quantitative approach method with a type of case-control study. The study started from June to July 2022 in 8 tofu factories with a license to operate for more than one year in Kupang City. Calculate the sample size using the Lemeshow formula. There are 46 workers divided into 23 case samples and 23 control samples with a ratio of 1:1. Based on the study results. It was shown that the variables that had a relationship with the incidence of contact dermatitis were personal hygiene, years of service, and frequency of contact. In contrast, the variables that had no association were the use of PPE, age, temperature, and humidity. Suggestions for tofu factory workers are that they can be expected to maintain personal hygiene and reduce the frequency of contact with chemicals to avoid susceptibility to skin diseases such as contact dermatitis.